Combining untargeted, targeted and sensory data to investigate the impact of storage on food volatiles: A case study on strawberry juice. (November 2018) - Buvé, Carolien; Neckebroeck, Bram; Haenen, Annelien; Kebede, Biniam; Hendrickx, Marc; Grauwet, Tara; Van Loey, Ann
Abstract: An integrated science-based approach, combining analytical and sensorial data and different data analysis methods, proved successful to study the impact of storage time, storage temperature and oxygen availability on strawberry juice volatiles and allowed to get a multi-perspective view on these changes. An untargeted GC–MS approach showed that the volatile fraction of shelf-stable strawberry juice clearly changed during ambient storage and that oxygen availability (linked to the type of bottle) had a limited effect. To gain further insight, several characteristic aroma compounds were quantified during storage at ambient (20 °C) and accelerated (28–42 °C) temperatures, kinetic parameters were estimated and odour activity values were calculated. The kinetic parameters showed that all characteristic aroma compounds changed significantly during storage at all temperatures and that the rate of change in some compounds was accelerated by storage at higher temperatures. The observed changes in strawberry juice volatiles caused sensorial differences between non-stored and 20 °C stored samples as shown by the sensory evaluations and odour activity values. Graphical abstract: Highlights: An integrated science-based approach is useful to study quality changes. The volatile profile of shelf-stable strawberry juice changed during storage. Humans notice differences in strawberry juice aroma upon ambient storage. Concentration changes of aroma compounds can affect consumer perception.